Life Experience of Human Immunodeficiency Virus (HIV) Sufferers: A Qualitative Systematic Review - RTS Netisa Martawinarti; Putri Irwanti Sari; Vivi Meiti Berhimpong (Universitas Airlangga, 2019)
Introduction: HIV is a chronic disease that continues to increase from year to year, with many symptoms or obstacles encountered by HIV sufferers when going about their day. The experience of HIV sufferers is important to know in order to find out what they have experienced for as long as they have had the disease. The objective of this qualitative systematic review is to describe the experiences of people living with HIV.Methods: The method used was searching for journals using the pre-determined keywords of ‘experience’, ‘living with HIV’ and ‘coping’ through the databases of Scopus, ProQuest, PubMed and Sage between 2014 and 2019.Results: The study results showed that there was still discrimination against people with HIV. They also experienced health problems due to the effects of the therapy, unpreparedness in accepting their conditions and the prevention of transmission to their family members.Conclusion: Understanding the role of uncertainty, stigma and resilience is important, since these factors may very well contribute to the patient’s mental health.